Gender‐specific outcomes of low‐dose computed tomography screening for lung cancer detection: A retrospective study in Chinese never‐smoker population - Huihong Wang; Jicheng Xie; Yahong Chen; Jiang Jin; Meixian Zhang; TaoHsin Tung; Youzu Xu (Cancer Medicine)
Abstract Objectives Low‐dose computed tomography (LDCT) has emerged as a pivotal tool for detecting lung cancer among ever‐smokers. This study aims to evaluate the gender‐specific outcomes of LDCT screening within the Chinese never‐smoking population. Methods We conducted a single‐center, retrospective cohort study, which analyzed LDCT screening outcomes for 42,018 asymptomatic participants. Specifically, we focused on assessing gender‐specific differences in the prevalence of pulmonary nodules, and the incidence of lung cancer diagnosis among never‐smokers. Results Among the 42,018 eligible participants, 41.50% were females and 58.50% were males. Most participants were non‐smokers (77.57%), with a significantly higher proportion of non‐smokers among females than males (99.33% vs. 62.14%). Pulmonary nodules were identified in 2.66% of participants, with a higher prevalence in females (2.99%) than males (2.43%) (p < 0.001). Non‐smoking females had a higher incidence of positive nodules than non‐smoking males (2.98% vs. 2.38%, p < 0.001). Invasive biopsies were performed in 334 individuals with nodules, confirming lung cancer in 258 cases. The majority of these cancer cases were non‐smokers (212), with non‐smoking females showing a higher incidence (0.85%) compared to males (0.43%) (p < 0.001). There was no significant difference in the false‐positive rates between non‐smoking females (0.14%) and males (0.13%). Multivariate analysis showed that never‐smoking women were more likely to undergo biopsies (OR 1.65, p = 0.0016) and had a higher, though not statistically significant, probability of lung cancer diagnosis (OR 1.84, p = 0.06). Conclusion This study elucidates sex‐based differences within the Chinese population, revealing a higher prevalence of pulmonary nodules and lung cancers among non‐smoking females. These findings offer valuable reference for both clinical practice and future research initiatives.